Thriving on chaos 45 tactics for a management revolution - Peters, Thomas J. (Chicago, Ill. : Nightingale-Conant, 1987)
Tom Peters describes forty-five tactics for bringing about a revolution in how companies are managed. The author maintains that this revolution is crucial to economic survival in the face of constantly changing conditions, such as new technologies, rapid fluctuations in currencies, disappearance of the mass market, and the proliferation in competitors.
Title from container.
Based on the book: Thriving on chaos / Tom Peters.
In container (30 cm.).
Keywords: Industrial management -- United States